Perlindungan Hukum terhadap Maternal Perinatal, Neonatal, dan Pemberian Asi Eksklusif Menurut Peraturan Menteri Kesehatan No. 97 Tahun 2014 dan Undang - Undang Kesehatan No. 36 Tahun 2009 - Dewi Iriani (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2017)
The number of maternal deaths, and infant deaths (perinatal and neonatal) has increased every year, so that there is no legal protection against maternal and infant deaths. As well as the large number of breastfeeding mothers who do not provide exclusive breastfeeding, the absence of local regulations governing lactation and the availability of lactation rooms The type of research is field Case studies in this study by knowing the legal protection of maternal, perinatal, and neonatal according to the Minister of Health Regulation No. 97 of 2014. Legal Protection of Exclusive Breastfeeding According to Health Law No. 36 of 2009 Minister of Health Regulation No. 97 of 2014. This regulation emphasizes that patients have the right to obtain health services, although it does not explicitly mention that patients get legal protection if doctors, midwives, hospitals are proven to have defaulted. Patients can make legal efforts and have the right to file a lawsuit and compensate material and immaterial damages in accordance with the Criminal Code and Civil Code. Exclusive Breastfeeding According to Health Law No. 36 of 2009. The law strictly regulates exclusive breastfeeding with strict sanctions for someone who prohibits breastfeeding for working women. In its implementation, there are still some breastfeeding mothers who work, only providing exclusive breastfeeding during maternity leave (2 months). As well as the absence of local regulations governing lactation and the unavailability of lactation rooms in public facilities.